Kontekstualisasi Hadis Makan Dengan Tiga Jari (Kajian Hadis Ghairu Tashri’ Perspektif Yusuf Al-Qardhawi) - Zainnurrofiq, Muhammad; Muhid, Muhid (Pascasarjana IAIN Metro, 2023)
The research focuses on Yusuf al-Qardhawi’s perspective on the practice of eating with three fingers in modern Islam. Using qualitative methods and a literature review, the study explores how Yusuf al-Qardhawi distinguishes between sunnah associated with Sharia law and those that are not, as well as sunnah that is general and eternal. In refining the concept of hadith ghairu tashri’, the research emphasises that sunnah is not merely confined to Sharia law but also has implications for ethics and morality. The importance of contextualising the hadith about eating with three fingers is key to understanding religious teachings in social, cultural, and current contexts to avoid extreme interpretations and acknowledge that the content of the hadith should not be taken only literally. Furthermore, the study emphasises the embedded educational values within it and underscores the urgency of sunnah as a universal guiding principle. This leads to a comprehensive understanding of the separation of sunnah and its relevance in contemporary Islam, expanding insights into the meaning and practical applications of sunnah in everyday life.